The rise and fall of Russia's Far Eastern republic, 1905-1922: nationalisms, imperialisms, and regionalisms in and after the Russian empire - Sablin, Ivan (Imperial transformations : Russian, Soviet and post-Soviet history, 2019)
Left-liberal nationalism and self-organization east of baikal, 1905-1916 -- Post-imperial particularisms in the Russian Far East, 1917-1919 -- Nationalisms and the making of the Far Eastern republic, 1920 -- The Far Eastern republic and the Priamur state formation, 1921 -- Competing nationalisms and sovietization in the Russian Far East, 1922